Significant enhancement of formic acid oxidation using rhodium nanostructures - Balan, Beena K.; Sathe, Bhaskar R. (Journal of Nanoscience and Nanotechnology, 2012)
The electrocatalytic activity of as-synthesized shape selective Rh nanostructures has been demonstrated using cyclic voltammetry, revealing unique shape-dependant performance towards HCOOH oxidation. interestingly, the enhancement factor (R) for different shapes of Rh with respect to that of commercial Rh towards formic acid oxidation ranges up to 20,000% for cubes as compared to 17,500% for pyramids and 11,000% for hexagons respectively. Mechanistic pathway for comparatively better sensitivity of cubes as compared to other shapes has been correlated with the results of X-ray diffraction.
Keywords: electrocatalysis; Formic Acid Oxidation; Preferential Growth; Rhodium Nanostructures